Molecular changes in skin pigmented lesions of the coral trout Plectropomus leopardus. (September 2016) - Lerebours, Adélaïde; Chapman, Emma C.; Sweet, Michael J.; Heupel, Michelle R.; Rotchell, Jeanette M.
Abstract: A high prevalence of skin pigmented lesions of 15% was recently reported in coral trout Plectropomus leopardus, a commercially important marine fish, inhabiting the Great Barrier Reef. Herein, fish were sampled at two offshore sites, characterised by high and low lesion prevalence. A transcriptomic approach using the suppressive subtractive hybridisation (SSH) method was used to analyse the differentially expressed genes between lesion and normal skin samples. Transcriptional changes of 14 genes were observed in lesion samples relative to normal skin samples. These targeted genes encoded for specific proteins which are involved in general cell function but also in different stages disrupted during the tumourigenesis process of other organisms, such as cell cycling, cell proliferation, skeletal organisation and cell migration. The results highlight transcripts that are associated with the lesion occurrence, contributing to a better understanding of the molecular aetiology of this coral trout skin disease. Highlights: Coral trout exhibit a high incidence of pigmented skin lesions at selected sampling sites. Genes from cell cycle, proliferation, and migration are differentially expressed in such lesions. Transcripts associated with the lesion occurrence may be used to determine aetiology.